2009
DOI: 10.1007/s12648-009-0018-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cobalt substitution on microstructure and magnetic properties in ZnO nanoparticles

Abstract: : Ferromagentic semiconductors have been actively pursued because of their potential as spin polarized carrier sources and easy integration into semiconductor technology. One such material, ZnO has been shown to be a potential Diluted Magnetic Semiconductor (DMS). The appearance of ferromagnetism, however, is found to be sensitive to the processing conditions. We report synthesis of ZnO nanoparticles of size ~20 nm by a simple co-precipitation technique using metal nitrates and NaOH as precipitant. The particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Previous work has demonstrated that for solid state reaction a complete solid solution of Co:ZnO can be achieved by addition of 0-20 wt% of Co 3 O 4 [11]. Since low amounts of cobalt (less than 5%) are not detectable by XRD technique, 10 wt% Co was used to insure complete formation of solid solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has demonstrated that for solid state reaction a complete solid solution of Co:ZnO can be achieved by addition of 0-20 wt% of Co 3 O 4 [11]. Since low amounts of cobalt (less than 5%) are not detectable by XRD technique, 10 wt% Co was used to insure complete formation of solid solution.…”
Section: Methodsmentioning
confidence: 99%
“…Co doped with ZnO has been synthesized via sol-gel [7], hydrothermal [8], wet chemical [9,10] and precipitation methods [11]. However, Co doped ZnO nanoparticles could be prepared by fast, simple and inexpensive solution combustion method [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, experimental observations of magnetism of the Co-doped ZnO synthesized by different methods have been controversial for both thin films and bulk samples. A number of groups observed no ferromagnetism in Zn 1−x Co x O [4][5][6], while Kalyana Lakshmi et al [7] and Maensiri et al [8] reported ferromagnetism in Co-doped ZnO powders. Kittilstved et al [9] and Rubi et al [10] demonstrated that ferromagnetism of n-type Zn 1−x Co x O thin films and powders could be switched on or off by chemical manipulation using nitrogen or oxygen, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…From micrographs, it is clear that the cauliflower like ZnO comprising of nanoclusters observed on the surface of the ZnO Nanoparticles and almost spherical shape morphology in doped ZnO. The morphological observation of SEM results indicates particles with less aggregation can be obtained from this method [18].…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 85%